The Role of Social Services in Poverty Reduction in Medan City - Sri Sudiarti; Siti Rama Hasibuan (Penerbit Jurnal Indonesia, 2022)
Poverty is one of the social problems that the social service program in Medan wants to overcome. Although poverty alleviation initiatives have been implemented, no evidence is available to explain their success. Regarding the research problem, this research was conducted with the aim of knowing more about the function of the social service of the city of Medan in poverty alleviation. The research method used is descriptive with a qualitative focus. Structured interviews, documentation studies of previous studies, relevant papers and literature, and observations were used to collect data and information. As a source of information, social service officers and related sectoral agencies are used. The results of the study indicate that the function of the social service of Medan City in alleviating poverty has not been maximized. This is because the number and quality of human resources are still limited, the budget is still not supported, coordination is still lacking, and the facilities and infrastructure needed for program implementation are still limited. The social service agency must improve program coordination and synergy with relevant agencies in the regions, as well as increase the intensity of discussions with provincial and central social services, based on research findings.